La bi-langue ou l’(en)jeu de l’écriture bilingue chez Abdelkebir Khatibi - Mabrour, Abdelouahed (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
“Quand j ’écris en français, ma langue maternelle se met en retrait: elle s ’écrase. Elle rentre au harem. Qui parle alors? Qui écrit? Mais elle revient (comme on dit). Et je travaille à la faire revenir quand elle me manque” (Khatibi 1978: 49). This statement made by Abdelkebir Khatibi, a Moroccan sociologist, poet and essayist, can clearly be seen in a number of his writings. In this article, we will attempt to examine closely the staging of this inter/trans-cultural experience that the author-narrator designates by a bilangue. Amour bilingue is a text in which romance and autobiography meet providing a suitable example of this peculiar, complex and priviliged situation which prevails in Morocco and on an extended scale, the Maghreb countries. The pro blematic (conceptual order) of bi/multi-lingualism coupled with a di/tri-glossia is treated by Khatibi under a fictional and poetic outlook. The bi-langue is considered by the author-narrated as a “between-two ”, a third language by means of which he succeeded in assuming the coexistence in him of a foreign language (the language of the other which no one still considers as a colonizing language anymore, the instrument of cultural uprooting) and of the mother tongue.